US Cystic Fibrosis Foundation and European Cystic Fibrosis Society consensus recommendations for the management of non-tuberculous mycobacteria in individuals with cystic fibrosis: executive summary. Issue 1 (16th December 2015) - Floto, R Andres; Olivier, Kenneth N; Saiman, Lisa; Daley, Charles L; Herrmann, Jean-Louis; Nick, Jerry A; Noone, Peadar G; Bilton, Diana; Corris, Paul; Gibson, Ronald L; Hempstead, Sarah E; Koetz, Karsten; et al.
Abstract : Non-tuberculous mycobacteria (NTM) are ubiquitous environmental organisms that can cause chronic pulmonary infection, particularly in individuals with pre-existing inflammatory lung disease, such as cystic fibrosis (CF). Pulmonary disease (PD) caused by NTM has emerged as a major threat to the health of individuals with CF, but remains difficult to diagnose and problematic to treat. In response to this challenge, the US Cystic Fibrosis Foundation (CFF) and the European Cystic Fibrosis Society (ECFS) convened a panel of 19 experts to develop consensus recommendations for the screening, investigation, diagnosis and management of NTM-PD in individuals with CF. PICO (population, intervention, comparison, outcome) methodology and systematic literature reviews were employed to inform draft recommendations, which were then modified to achieve consensus and subsequently circulated for public consultation within the USA and European CF communities. We have thus generated a series of pragmatic, evidence-based recommendations as an initial step in optimising management for this challenging condition.